2018
DOI: 10.7567/jjap.57.045501
|View full text |Cite
|
Sign up to set email alerts
|

Erosion of fluorinated diamond-like carbon films by exposure to soft X-rays

Abstract: The effects of soft X-ray irradiation on fluorinated diamond-like carbon (F-DLC) films were investigated using synchrotron radiation (SR). The Vickers hardness of the F-DLC films substantially increased from an initial value of about 290 to about 800 HV at a dose of 50 mA·h and the remained constant at about 1100 HV at doses of more than 300 mA·h. This dose dependence was consistent with those of the film thickness and elemental composition. The depth profile of the elemental composition inside each F-DLC film… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…The nanocomposite DLC films are capable of delaying the occurrence of this change and maintaining a relatively low lifetime. For example, although soft X-rays influence the whole F-DLC film instead of just the outermost surface, a low F content contributes to resisting soft X-ray irradiation [104,105]. Similarly, the presence of Si doping could restrict the desorption of hydrogen by X-ray irradiation [106,107].…”
Section: Research Status Of Dlc Filmmentioning
confidence: 99%
“…The nanocomposite DLC films are capable of delaying the occurrence of this change and maintaining a relatively low lifetime. For example, although soft X-rays influence the whole F-DLC film instead of just the outermost surface, a low F content contributes to resisting soft X-ray irradiation [104,105]. Similarly, the presence of Si doping could restrict the desorption of hydrogen by X-ray irradiation [106,107].…”
Section: Research Status Of Dlc Filmmentioning
confidence: 99%
“…[11] Kanda et al studied the erosion of the fluorinated DLC films exposed to soft X-rays and found that the radiation can cause the uniform decrease in fluorine composition from film surface to substrate. [12] However, the erosion behaviors of DLC films caused by hard particles, which can cause severe mass loss, has been rarely reported in literature, leading to the unclear erosion mechanisms of these films.…”
Section: Introductionmentioning
confidence: 99%